Identifikasi dan Inventarisasi Genotip Tanaman Ubi kayu (Manihot esculenta Crantz) di Kabupaten Serdang Bedagai Sumatera Utara - Muhammad Fauzi; Emmy Harso Kardhinata; Lollie Agustina P Putri (Jurnal Agroekoteknologi, 2015)
The objective of this research was to document and characterize phenotypically cassava genotypes. Using survey methodology, the sample of cassava genotypes were collected from three sub-districts of Serdang Bedagai Regency, i.e. Perbaungan, Serbajadi, and Dolok Masihul with three villages for each sub-district, i.e. Jambur Pulau, Suka Jadi, Lidah Tanah, Tanjung Harap, Kuala Bali, Karang Tengah, Dolok Manampang, Kota Tengah, and Kampung Mangga. This descriptor list aims at helping to standardize characterization data was taken from National Commision for Genetic Resources 2014 i.e; the ratio of lobe length to lobe width of of central leaf lobe, number of leaf lobe, petiole length, petiole color, plant height, distance between lef scar, color of upper stem, color of stem exterior, color of stem epidermis, diameter of cassava root, length of cassava root, number of cassava root/plant, average of cassava root weight, and cassava productivities. The result of research showed the specific characteristics of cassavas which have different lower and upper stem in case of color which were green, reddish green, grey, and amber; different colors of cassava root cortex which were rose/ white, yellow, and amber. The result obtained 7 genotypes of cassava that with various local name depend on the lecation i,e; Malaysia, Roti, Adira-1, Kalimantan (Banjar), Valencia, Lampung and Pulut.Keywords: Cassava, identification, inventarisation